Beyond Trump? A critique of Nancy Fraser's call for a new left hegemony. (December 2019) - Isaac, Jeffrey C.
Nancy Fraser's essay 'From Progressive Neoliberalism to Trump – and Beyond' is an important intervention in current discussions of Trumpism and how the left, broadly, should understand and respond to it. Fraser's piece is an admirable effort to situate Trumpism in a broader and deeper political–economic context. At the same time, her argument suffers from a kind of reductionism and takes comfort from a questionable grand narrative of emancipation that is difficult any longer to take seriously. It thus warrants both careful attention and serious criticism. My basic political point: Fraser's version of 'socialism or barbarism' is unconvincing, and the adamant and principled defence of liberal democracy, and its further reform, ought to be a priority for left liberals and leftists more generally who are serious about countering right-wing populist authoritarianism.